The Roles and Challenges of Micro Finance in Women Empowerment: A Case Study in Oromia Credit and Saving Institution in West Shoa Zone, Ethiopia - Gebisa, Diriba Ayele; Dassa, Aman Rikitu (International Journal of Small and Medium Enterprises, 2019)
Empowerment of women has emerged as an important issue in recent times since women remained disadvantaged part of society for a long period of times. Empowerment of women facilitates development by the uplifting their economic, social and political status. Microfinance is proved to be the instrument to handle poverty that exists mostly in urban and rural areas of the country. It is treated as a key strategy in addressing development issues across the country since the last decade. This study basically attempts to analyze the roles and challenges of microfinance in women empowerment. A primary survey has been carried out to capture the realistic experiences from the women beneficiaries of Oromia Micro Credit and Saving Institution of West Shoa Zone branch. In order to address the objectives of the study, a mixed approach has been adopted and primary data were collected and analyzed using quantitative and qualitative analysis techniques. A total sample of 268 women customers’ was selected using simple random sampling technique out of 1316 target populations. Data collected from these respondents were analyzed and interpreted using percentage, weighted mean and mean ranking and the hypothesis was tested using the paired t-test. The findings showed that a significant number of clients had increased their income, saving, decision making and asset ownership rights and safeguarded themselves and their families from financial difficulties. Besides its role, the main challenging factors are unproductive usages of the loan, limited loan size, lack of training and follow up, low awareness and high-interest rate of the loan.